-12÷n=3

Rewrite the division as a fraction.

-12n=3

Move the negative in front of the fraction.

-12n=3

-12n=3

Multiply each term by n and simplify.

Multiply each term in -12n=3 by n.

-12n⋅n=3⋅n

Cancel the common factor of n.

Move the leading negative in -12n into the numerator.

-12n⋅n=3⋅n

Cancel the common factor.

-12n⋅n=3⋅n

Rewrite the expression.

-12=3⋅n

-12=3n

-12=3n

Rewrite the equation as 3n=-12.

3n=-12

Divide each term by 3 and simplify.

Divide each term in 3n=-12 by 3.

3n3=-123

Cancel the common factor of 3.

Cancel the common factor.

3n3=-123

Divide n by 1.

n=-123

n=-123

Divide -12 by 3.

n=-4

n=-4

n=-4

Solve for n -12÷n=3